2020
DOI: 10.1186/s43055-020-00256-5
|View full text |Cite
|
Sign up to set email alerts
|

Additional diagnostic role of MRI spectroscopy, diffusion and susceptibility imaging in differentiation of CPA masses: our experience with emphasis on schwannomas and meningiomas

Abstract: Background CPA masses are uncommon lesions and usually have quite distinctive imaging features. Still, diagnosis can be challenging in some cases, carrying a significant impact on the choice of treatment and surgical approach. The purpose of this study was to validate the usefulness of MRI spectroscopy, diffusion, and susceptibility in the characterization of CPA masses with the emphasis on the two commonest lesions: schwannomas and meningiomas. Results The study included a total of 27 cases: schwannomas (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…In more ambiguous cases, a higher ADC value in large neurogenic tumors may be a distinguishing feature from other cerebellopontine angle tumors including meningiomas, which is related to a larger proportion of loose-textured and cystic areas (i.e., Antoni B tissue) [ 23 , 24 ]. It is also suggested that the presence of non-calcification microbleeds, which is also present in our reported case, as well as a myoinositol peak in magnetic resonance spectroscopy, are features for differentiating schwannoma from meningioma [25] .…”
Section: Discussionsupporting
confidence: 72%
“…In more ambiguous cases, a higher ADC value in large neurogenic tumors may be a distinguishing feature from other cerebellopontine angle tumors including meningiomas, which is related to a larger proportion of loose-textured and cystic areas (i.e., Antoni B tissue) [ 23 , 24 ]. It is also suggested that the presence of non-calcification microbleeds, which is also present in our reported case, as well as a myoinositol peak in magnetic resonance spectroscopy, are features for differentiating schwannoma from meningioma [25] .…”
Section: Discussionsupporting
confidence: 72%
“…These MRS findings were quite similar to primary CNS lymphoma magnetic resonance spectroscopy (MRS) features, which are a significant rise of choline, NAA, and creatine decrease, high Choline/Creatine (Cho/Cr) and Choline/N-acetylaspartate (Cho/NAA) ratios and lipidic peak [ 2 , 3 , 5 , 7 ]. MRS helps to differentiate primary CNS lymphoma from other lesions, such as acoustic neuroma and meningioma: in fact, acoustic neuroma shows myo-inositol peak and high choline peak; myo-inositol peak is maybe related to microglial activation and astrogliosis, a feature that is observed in this lesion [ 2 , 3 , 11 ]. On MRS meningioma spectra are marked by an alanine peak, high choline peak, glutamate (Glu) peak, and low NAA peak; its higher alanine/creatine ratios are useful to differentiate it from other intracranial neoplasms [ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRS helps to differentiate primary CNS lymphoma from other lesions, such as acoustic neuroma and meningioma: in fact, acoustic neuroma shows myo-inositol peak and high choline peak; myo-inositol peak is maybe related to microglial activation and astrogliosis, a feature that is observed in this lesion [ 2 , 3 , 11 ]. On MRS meningioma spectra are marked by an alanine peak, high choline peak, glutamate (Glu) peak, and low NAA peak; its higher alanine/creatine ratios are useful to differentiate it from other intracranial neoplasms [ 3 , 11 ]. MRS findings may not be useful to distinguish primary CNS lymphoma from glioblastoma and metastases, but some authors reported higher Glu/Cr, Cho/Cr, and glutamate/glutamate+glutamine (Glu/Glu+Gln) ratios in primary CNS lymphoma than in glioblastoma [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuberculous brain abscess can be diagnosed only through histopathologic examination as neuroimaging is non-specific. Different studies have been conducted on the use of in vivo proton MR spectroscopy for specifying pyogenic brain abscess and differentiating between brain abscess and glioblastoma multiforme (4)(5)(6)(7)(8)(9) . The cause of brain abscesses can not be specified using conventional MR imaging.…”
Section: Introductionmentioning
confidence: 99%